A Machine‐Fabricated 3D Honeycomb‐Structured Flame‐Retardant Triboelectric Fabric for Fire Escape and Rescue. Issue 38 (16th August 2020) - Ma, Liyun; Wu, Ronghui; Liu, Sai; Patil, Aniruddha; Gong, Hao; Yi, Jia; Sheng, Feifan; Zhang, Yuzei; Wang, Jiang; Wang, Jun; Guo, Wenxi; Wang, Zhong Lin
Abstract: Fire disaster is one of the most common hazards that threaten public safety and social development: how to improve the fire escape and rescue capacity remains a huge challenge. Here, a 3D honeycomb‐structured woven fabric triboelectric nanogenerator (F‐TENG) based on a flame‐retardant wrapping yarn is developed. The wrapping yarn is fabricated through a continuous hollow spindle fancy twister technology, which is compatible with traditional textile production processes. The resulting 3D F‐TENG can be used in smart carpets as a self‐powered escape and rescue system that can precisely locate the survivor position and point out the escape route to timely assist victim search and rescuing. As interior decoration, the unique design of the honeycomb weaving structure endows the F‐TENG fabric with an excellent noise‐reduction ability. In addition, combining with its good machine washability, air permeability, flame‐retardency, durability, and repeatability features, the 3D F‐TENG may have great potential applications in fire rescue and wearable sensors as well as smart home decoration. Abstract : A multifunctional 3D honeycomb‐structure fabric triboelectric nanogenerator (3D F‐TENG) is fabricated from yarn to fabric by scalable and continuous textile fabrication technology. The 3D F‐TENG can be used as a smart indoor carpet, which has functions of flame retardancy, noise reduction, precise rescue location, and real‐time route guidance under fire conditions.